Silicone adsorption film

CN115003503BActive Publication Date: 2026-10-23FUJI COPIAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180011044.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-07
Filing Date
2021-02-03
Publication Date
2026-10-23
Estimated Expiration
2041-02-03

AI Technical Summary

Benefits of technology

[0011]根据本发明,提供一种平滑面上的吸附性、和剥离后的平滑面上的残胶抑制性两者优异的有机硅吸附膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003764738220000071
    Figure BDA0003764738220000071
  • Figure BDA0003764738220000191
    Figure BDA0003764738220000191
  • Figure BDA0003764738220000201
    Figure BDA0003764738220000201
Patent Text Reader

Abstract

The present invention provides a silicone adsorption film which is excellent in both adsorptivity on a smooth surface and residue inhibition on a smooth surface after peeling. A silicone adsorption film comprising a base material layer, and a silicone adsorption layer stacked on the base material layer, the silicone adsorption layer being a cured product of a cross-linkable composition, the cross-linkable composition comprising (a) a cross-linkable organopolysiloxane, (b) a cross-linking agent, (c) a non-reactive MQ resin, and (d) a reactive MQ resin, the silicone adsorption film being excellent in both adsorptivity on a smooth surface and residue inhibition on a smooth surface after peeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to silicone adsorption membranes. Specifically, it relates to silicone adsorption membranes that are adhered to and peeled off from a smooth surface, exhibiting excellent adsorption properties on the smooth surface and excellent residue inhibition on the peeled surface. Preferably, this invention relates to silicone adsorption membranes used to fix a polishing pad via a platform of a polishing apparatus and a polishing pad, exhibiting excellent adsorption properties on the platform of the polishing apparatus and excellent residue inhibition on the peeled platform. Background Technology

[0002] In the manufacturing processes of semiconductor components and electronic components such as semiconductor wafers, hard disk substrates, and glass substrates for displays, grinding is performed to planarize or mirror-finish the substrate surface. In these grinding processes, a grinding pad is fixed to the platform of a grinding apparatus, abrasive slurry is supplied to the surface of the grinding layer of the grinding pad, and the component being ground slides against the grinding pad under pressure. To improve the efficiency of grinding pad replacement and fixing operations, as disclosed in Patent Document 1, a self-adhesive material made of silicone resin has traditionally been used as the material for the adsorption layer in grinding pads that sequentially stack an adsorption layer, a substrate, and a grinding layer.

[0003] The silicone adsorption layer, made of self-adhesive material from silicone resin, generally does not easily shift relative to the direction parallel to the bonded surface, and also exhibits strong adsorption relative to the direction perpendicular to the bonded surface. Furthermore, it also possesses the property of being easily peeled off from the ends of the silicone adsorption layer. Moreover, if the silicone adsorption layer peeled off from the bonded surface is re-attached to the bonded surface, it will once again firmly adhere to the bonded surface. This property of easily peeling off from the bonded surface, along with the property of firmly adsorbing back onto the bonded surface, is collectively referred to as reprocessability.

[0004] Through this reprocessability, the silicone adsorption layer, when used to fix the polishing pad, can be easily peeled off from the platform of the polishing apparatus when the polishing pad is replaced. Even if the polishing pad is attached in the wrong position, it can be easily reattached. Furthermore, even if temporarily peeled off from the platform, it can be firmly adhered upon reattachment, thus continuously fixing the polishing pad during polishing. Therefore, the silicone adsorption layer significantly contributes to the efficiency of polishing pad replacement and fixing operations. Existing technical documents Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-108498 Summary of the Invention The problem that the invention aims to solve

[0006] In recent years, the need for increased efficiency in grinding operations has led to demands for higher speeds. However, this high-speed grinding process increases the load on the adsorption layer of the grinding pad, resulting in a greater load on the silicone adsorption layer in the direction parallel to the bonded surface. Consequently, partial delamination of the silicone adsorption layer is more likely. Even when partial delamination occurs, the grinding pad cannot be stably and continuously held in place, hindering the desired grinding of non-grinding components. Furthermore, the entry of grinding powder into the delaminated area can impair reprocessability.

[0007] In order to prevent partial peeling of the grinding pad during high-speed grinding operations by increasing the adsorption force of the silicone adsorption layer, the inventors attempted to incorporate a non-reactive MQ resin into the curable (crosslinkable) composition forming the silicone adsorption layer. However, if the adsorption force of the silicone adsorption layer is increased in this way, when the silicone adsorption layer is peeled off to replace the grinding pad, the problem of silicone residue (so-called adhesive residue) arises on the bonding surface (platform). If adhesive residue is formed on the platform, the silicone adsorption layer of the subsequently attached grinding pad cannot adhere tightly to the platform, so the grinding pad is easily peeled off. In addition, the grinding pad is tilted and fixed relative to the workpiece being ground, which prevents the grinding pad from applying uniform pressure to the workpiece being ground, and sometimes prevents the workpiece from being ground to achieve the desired grinding effect. Thus, the silicone adsorption layer adsorbed on a smooth surface such as a platform cannot essentially achieve both increased adsorption on the smooth surface and suppression of adhesive residue on the smooth surface after peeling, and cannot adequately meet the requirements of high-speed grinding operations themselves.

[0008] Therefore, the object of the present invention is to provide an organosilicon adsorption membrane that has excellent adsorption properties on a smooth surface and excellent residual adhesive inhibition properties on the smooth surface after peeling. Methods for solving problems

[0009] Through in-depth research, the inventors discovered that by combining non-reactive MQ resin and reactive MQ resin in combination with crosslinking polyorganosiloxane and a crosslinking agent as a crosslinking composition for forming an organosilicon adsorption layer, an organosilicon adsorption film was obtained that exhibits excellent adsorption properties on a smooth surface and residual adhesive inhibition properties on the smooth surface after peeling. Based on these insights, the inventors conducted further and repeated research, thereby completing this invention.

[0010] That is, the present invention provides an invention in the manner described below. Item 1. An organosilicon adsorption membrane, comprising a substrate layer and an organosilicon adsorption layer laminated on the substrate layer, The aforementioned organosilicon adsorption layer is a cured product of a crosslinking composition, which comprises (a) a crosslinking organopolysiloxane, (b) a crosslinking agent, (c) a non-reactive MQ resin, and (d) a reactive MQ resin. Item 2. The organosilicon adsorption membrane according to Item 1, wherein, relative to the total amount of component (a) and component (b) above 100 parts by weight, it comprises 43 to 100 parts by weight of component (c) above and 1.1 to 10.6 parts by weight of component (d) above. Item 3. The organosilicon adsorption membrane according to item 1 or 2, wherein the above-mentioned component (a) is a diorganopolysiloxane containing two or more alkenyl groups in one molecule. Item 4. The organosilicon adsorption membrane according to any one of items 1 to 3, wherein the component (b) above is an organohydrogen polysiloxane. Item 5. The organosilicon adsorption membrane according to any one of items 1 to 4, wherein the thickness of the organosilicon adsorption layer is 15 to 30 μm. Item 6. The organosilicon adsorption membrane according to any one of items 1 to 5, wherein the storage modulus of the organosilicon adsorption layer is 5 × 10⁻⁶. 4 ~15×10 4 Pa. Item 7. The organosilicon adsorption membrane according to any one of items 1 to 6, wherein an anchoring layer is included between the substrate layer and the organosilicon adsorption layer, the anchoring layer being selected from polyester resin, acrylic resin and polyurethane resin. Item 8. The organosilicon adsorption membrane according to any one of items 1 to 7, wherein the organosilicon adsorption membrane is used to fix the organosilicon adsorption layer on the platform of the grinding apparatus and to fix the grinding pad on the substrate layer side. Invention Effects

[0011] According to the present invention, an organosilicon adsorption membrane with excellent adsorption properties on a smooth surface and excellent residual adhesive inhibition properties on the smooth surface after peeling is provided. Attached Figure Description

[0012] Figure 1 An example of the layered structure of an organosilicon adsorption membrane is shown. Figure 2 An example of the layered structure of an organosilicon adsorption membrane is shown. Figure 3 An example of the layered structure of an organosilicon adsorption membrane is shown. Figure 4 An example of the state of the organosilicon adsorption membrane before use is shown. Figure 5 An example of the state of the organosilicon adsorption membrane before use is shown. Figure 6 Examples of how organosilicon adsorption membranes are used are shown. Detailed Implementation

[0013] The organosilicon adsorption membrane of the present invention is characterized in that it comprises a substrate layer and an organosilicon adsorption layer laminated on the substrate layer, wherein the organosilicon adsorption layer is a cured product of a crosslinked composition comprising (a) a crosslinked organopolysiloxane, (b) a crosslinking agent, (c) a non-reactive MQ resin, and (d) a reactive MQ resin. Hereinafter, the organosilicon adsorption membrane of the present invention will be described in detail.

[0014] Layer structure and usage An example of the layer composition of an organosilicon adsorption membrane is shown in Figures 1-3 The organosilicon adsorption membrane of the present invention is as follows: Figure 1 The silicone adsorption membrane 10 shown is a laminate comprising a substrate layer 1 and a silicone adsorption layer 2 directly laminated on the substrate layer 1. Furthermore, the silicone adsorption membrane of the present invention, as... Figure 2 Like the organosilicon adsorption membrane 10a shown, it can be used... Figure 1 The substrate layer 1 side of the organosilicon adsorption membrane 10 further has an adhesive layer 3. Furthermore, the organosilicon adsorption membrane of the present invention, as... Figure 3 As shown in the diagram, the silicone adsorption film 10b can be a laminate comprising a substrate layer 1 and a silicone adsorption layer 2 laminated on the substrate layer 1 with an anchoring layer 4 in between. Furthermore, although not shown, in Figure 3 In the organosilicon adsorption membrane 10b shown, further as... Figure 2 Like the silicone adsorption film 10a, it further has adhesiveness 3 on the substrate layer 1 side.

[0015] The organosilicon adsorbent membrane of the present invention can be laminated with additional layers to protect the adhesive layer until it is used. For example, in Figure 2 In the case of the organosilicon adsorption membrane 10a shown, as Figure 4 As shown, a release film 20 having a substrate layer 5 can be laminated on the silicone adsorption layer 2, and a cover film 30 having a substrate layer 7 and a release layer 8 can be laminated on the adhesive layer 3. Further, as... Figure 5 As shown, a release film 20a having a substrate layer 5 and a release layer 6 can be laminated on the silicone adsorption layer 2, and a cover film 30 having a substrate layer 7 and a release layer 8 can be laminated on the adhesive layer 3. The release films 20, 20a and the cover film 30 are peeled off when using the silicone adsorption film 10a.

[0016] The organosilicon adsorption membrane of the present invention is used by adsorbing the organosilicon adsorption layer on two sides onto a smooth surface. For example, in Figure 2 In the case of the organosilicon adsorption membrane 10a shown, preferably, as Figure 6 As shown, the silicone adsorption layer 2 is adsorbed onto the platform S, and the abrasive member P is bonded to the adhesive layer 3, thereby fixing the abrasive member P on the platform S.

[0017] Substrate layer As the material for the substrate layer, various plastics can be used without particular limitation, including, for example, polyolefins (polyethylene, polypropylene, etc.), polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, copolyesters, etc.), polyamides (nylon 6, nylon 66, copolymers of nylon 6 and nylon 66, nylon 6,10, poly(m-phenylene adipamide (MXD6) etc.), polycarbonate, triacetyl cellulose, fluoropolymers, polyphenylene ether, polyimide, polyamide-imide, acrylic resins, polyvinyl chloride, polyvinylidene chloride, polyacrylonitrile, etc. Among these, from the viewpoint of processability and cost during thermal crosslinking of the crosslinking composition forming the organosilicon adsorption layer, polyester and polycarbonate are preferred, and from the viewpoint of transparency, polyester is more preferred, and polyethylene terephthalate is even more preferred.

[0018] The thickness of the substrate layer is not particularly limited, but can be typically 5 to 400 μm, preferably 20 to 250 μm, more preferably 30 to 150 μm, and even more preferably 40 to 80 μm.

[0019] As a specific example of a substrate layer, a film formed from the aforementioned materials can be cited.

[0020] To improve the adhesion to the silicone adsorption layer or the anchoring layer provided as needed, and / or to impart antistatic properties, the surface of the substrate layer may be modified by plasma treatment or flame treatment, preferably plasma treatment.

[0021] Organosilicon adsorption layer The organosilicon adsorbent layer is a cured product of a crosslinked composition comprising (a) a crosslinked organopolysiloxane (hereinafter also referred to as component (a)), (b) a crosslinking agent (hereinafter also referred to as component (b)), (c) a non-reactive MQ resin (hereinafter also referred to as component (c)) and (d) a reactive MQ resin (hereinafter also referred to as component (d)).

[0022] The silicone adsorption layer has the flexibility and self-adhesion of rubber. It is composed of a cured product of the above-mentioned cross-linked composition, which has the excellent effects of both adsorption on the smooth surface and residual adhesive inhibition on the smooth surface after peeling.

[0023] (a) Crosslinked organopolysiloxanes) As component (a), namely crosslinked organopolysiloxane, there is no particular limitation as long as it is an organopolysiloxane having crosslinked groups, and preferred examples are diorganopolysiloxanes having two or more alkenyl groups in one molecule.

[0024] In a diorganopolysiloxane having two or more alkenyl groups in one molecule, the structure of the diorganosiloxane moiety can be exemplified by a linear structure having a main chain containing repeating diorganosiloxane units, or, depending on the case, a branched structure having branches containing diorganosiloxane or repeating diorganosiloxane units. Furthermore, in a diorganopolysiloxane having two or more alkenyl groups in one molecule, the bonding site of the alkenyl groups is not particularly limited; examples include the ends of the diorganosiloxane moiety. More specifically, examples include only the two ends of a linear diorganopolysiloxane; only the two ends of the main chain of a branched diorganopolysiloxane; or the two ends of the main chain and the ends of the side chains of a branched diorganopolysiloxane.

[0025] Specific examples of organopolysiloxanes having two or more alkenyl groups in one molecule used in this invention are shown in formulas (1-1) to (1-3) and (2) below. Formulas (1-1) to (1-3) below are examples of linear organopolysiloxanes having two alkenyl groups in one molecule, and formula (2) below is an example of branched organopolysiloxanes having two or more alkenyl groups in one molecule.

[0026] [Chemical Formula 1]

[0027] In equations (1-1) to (1-3) and (2), R 1 The groups represent organic groups that can be chosen to be the same or different from each other, where X represents an alkenyl group, and n, m, and l represent integers.

[0028] As R 1 Preferred examples include alkyl groups with 1 to 10 carbon atoms, preferably 1 to 6, and more preferably methyl, ethyl, propyl, etc.; cycloalkyl groups; cyclopentyl, cyclohexyl, cycloheptyl, etc.; aryl groups such as phenyl, tolyl, xylyl, naphthyl, biphenyl, etc.; aralkyl groups such as benzyl, phenylethyl, phenylpropyl, methylbenzyl, etc.; and groups obtained by substituting at least a portion of the hydrogen atoms bonded to the carbon atoms of these groups with halogen atoms such as fluorine, chlorine, bromine, or cyano, etc., preferably alkyl groups, and more preferably methyl groups. In particular, compounds of formulas (1-1) to (1-3) and (2) preferably contain at least 50% R in one molecule. 1 Occupied by methyl groups.

[0029] Preferred examples of X include alkenyl groups with 2 to 8 carbon atoms, preferably vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, and cyclohexenyl, with vinyl being more preferred. It should be noted that the compound of formula (2) has one alkenyl group at each end, except that the polyorganosiloxane portion is branched, which is the same as that of the straight-chain formula (1-1). However, it can also be changed to have two or three alkenyl groups at each end, just like formulas (1-2) and (1-3).

[0030] n is an integer greater than or equal to 0 (in the case of equations (1-1) to (1-3)) or an integer greater than or equal to 1 (in the case of equation (2)), m is an integer greater than or equal to 0, and l is an integer greater than or equal to 1. Furthermore, it is preferable that n and m satisfy 10 ≤ n + m ≤ 10,000, and more preferably 50 ≤ n + m ≤ 2,000.

[0031] These crosslinked organopolysiloxanes can be used alone or in combination.

[0032] From the viewpoint of optimal curability and adhesion, the weight-average molecular weight (Mw) of crosslinkable organopolysiloxanes can be 20,000 or more, preferably 50,000 or more, and more preferably 70,000 or more. From the viewpoint of ensuring a viscosity that is not too high to facilitate stirring during manufacturing, it can be, for example, 600,000 or less, preferably 300,000 or less, and more preferably 100,000 or less. It should be noted that the weight-average molecular weight Mw is the converted molecular weight of polystyrene determined by gel permeation chromatography (GPC). The definitions of Mn and Mw are described in "Fundamentals of Polymer Chemistry" (edited by the Polymer Society, Tokyo Chemical Association, 1978), etc., and can be calculated from the molecular weight distribution curve based on GPC (the same applies below).

[0033] (b) Crosslinking agent) As component (b), i.e., the crosslinking agent, there are no particular limitations as long as it has a hydrosilicone group (SiH group) for crosslinking component (a). Through crosslinking, the silicone adsorbent layer has rubber-like flexibility, which enables excellent adhesion between the silicone adsorbent layer and the substrate.

[0034] Organohydropolysiloxanes are preferably used as crosslinking agents. Organohydropolysiloxanes can be any of the following resinous substances with a linear, branched, cyclic, or three-dimensional network structure containing two or more, preferably three or more, hydrosilane groups in one molecule. Specific examples of such organohydropolysiloxanes are shown in the following average composition formula (3).

[0035] [Chemical Formula 2] H a R 2 b SiO(4-a-b) / 2 (3)

[0036] In equation (3), R 2 Let a and b be any unsubstituted or substituted monovalent hydrocarbon groups that are either identical or different and do not contain aliphatic unsaturated bonds. Let a and b be numbers that satisfy 0 < a < 2, 0.8 ≤ b ≤ 2, and 0.8 < a + b ≤ 3.

[0037] As unsubstituted or substituted monovalent hydrocarbon groups without aliphatic unsaturated bonds, examples include those in equations (1-1) to (1-3) and equation (2) as R. 1 The exemplified groups.

[0038] These organohydrogen polysiloxanes can be used alone or in combination. Preferably, component (b) comprises less than 50% by weight of an organohydrogen polysiloxane having two hydrosilane groups per 100% of its total weight, and the remainder comprises an organohydrogen polysiloxane having at least three hydrosilane groups.

[0039] From the viewpoint of facilitating addition reactions, the weight-average molecular weight (Mw) of the crosslinking agent can be, for example, 200 or more, preferably 500 or more, and more preferably 1,000 or more. From the viewpoint of preventing the organosilicon adsorption layer from becoming excessively soft, it can be, for example, 15,000 or less, preferably 5,000 or less, and more preferably 1,500 or less.

[0040] As for the amount of component (b), relative to 1 mole of component (a), examples can be given that the amount of hydrogen atoms in component (b) reaches, for example, 0.5 to 4 moles, preferably 1 to 2.5 moles.

[0041] (c) Non-reactive MQ resin) (c) Components, namely non-reactive MQ resin, contain M units (R 3 3SiO 1 / 2 ) and Q unit (SiO4· 1 / 2 The present invention comprises an organosilicon resin that does not contain reactive functional groups such as vinyl or hydroxyl groups within its molecule. If component (c) is incorporated, the adsorption capacity of the organosilicon adsorption layer is improved. Conversely, during the curing of the crosslinking composition, the reaction between the crosslinking groups of component (a) and the hydrosilane groups of component (b) is hindered, resulting in unreacted hydrosilane groups that cause residue buildup. However, in this invention, the organosilicon adsorption layer, while containing component (c), also achieves excellent residue suppression.

[0042] In the M unit that constitutes the non-reactive MQ resin, R 3It can be any unsubstituted or substituted hydrocarbon group with 1 to 10 carbon atoms, either the same or different. Specifically, examples include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, and octyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; and aryl groups such as phenyl, tolyl, xylyl, and naphthyl. Alkyl groups are preferred, and methyl groups are more preferred.

[0043] In non-reactive MQ resins, from the viewpoint of improving the adsorption of the organosilicon adsorption layer, the molar ratio of M units to Q units (M unit / Q unit) can be 0.6 or more, and from the viewpoint of improving the inhibition of residual adhesive, it can be 1.8 or less.

[0044] These non-reactive MQ resins can be used alone or in combination.

[0045] From the viewpoint of improving the adsorption capacity of the organosilicon adsorption layer, the weight-average molecular weight (Mw) of the non-reactive MQ resin can be, for example, 100,000 or more, preferably 150,000 or more, and more preferably 170,000 or more. From the viewpoint of preventing plastic deformation of the organosilicon adsorption layer, it can be, for example, 300,000 or less, preferably 250,000 or less, and more preferably 200,000 or less.

[0046] In the crosslinking composition, the content of component (c) relative to 100 parts by weight of the total amount of components (a) and (b) can be 43 to 100 parts by weight. From the viewpoint of improving the adsorption of the organosilicon adsorption layer, the content of component (c) is preferably 43 parts by weight or more, and from the viewpoint of improving residue inhibition, it is preferably 100 parts by weight or less. From the viewpoint of further obtaining these effects or further improving peelability, it is preferably 61 to 100 parts by weight, more preferably 78 to 100 parts by weight, and even more preferably 90 to 100 parts by weight.

[0047] (d) Reactive MQ resin) Component (d), namely the reactive MQ resin, is an MQ resin containing M and Q units and having silanol groups within its molecule. By incorporating component (d) into the crosslinking composition, the unreacted hydrosilane groups remaining due to the presence of component (c) during the curing of the crosslinking composition react with the silanol groups of component (d), thereby reducing residue. Therefore, residue can be prevented without reducing the adsorption capacity of the silicone adsorption layer enhanced by component (c). Furthermore, although component (d) is not as effective as component (c), it also enhances the adsorption capacity of the silicone adsorption layer.

[0048] Reactive MQ resin is a resin containing M 1 Unit ((OH))c R 4 (3-c) SiO 1 / 2 ) and M depending on the situation 2 Unit (R) 5 3SiO 1 / 2 ) and Q unit (SiO4· 1 / 2 M is an organosilicon resin. 1 In the unit, R 4 M is any unsubstituted or substituted hydrocarbon group with 1 to 10 carbon atoms, either the same or different. 2 In the unit, R 5 R is any unsubstituted or substituted hydrocarbon group with 1 to 10 carbon atoms, either the same or different. 4 and R 5 Specific examples can be given as R in component (c), i.e., non-reactive resin. 3 The illustrated group. Furthermore, c is an integer from 1 to 3, preferably 1 or 2, and more preferably 1.

[0049] In reactive MQ resin, as relative to M 1 The OH group and R of the unit 4 Base and M 2 Unit R 5 From the viewpoint of further improving the effect of preventing residual adhesive, the proportion of OH groups in the total amount of OH groups can be 0.5 mol% or more, preferably 1 mol% or more. From the viewpoint of further improving the adsorption properties of the organosilicon adsorption layer, it can be 10 mol% or less, preferably 5 mol% or less.

[0050] In reactive MQ resin, as M 1 Unit and M 2 The total molar ratio of unit to Q unit ((M) 1 Unit + M 2 From the viewpoint of further improving the effect of preventing residual adhesive, the value of Q unit is 0.5 or more, preferably 0.6 or more. From the viewpoint of further improving the adsorption capacity of the organosilicon adsorption layer, the value of Q unit is 1.2 or less, preferably 0.9 or less.

[0051] These reactive MQ resins can be used alone or in combination.

[0052] From the viewpoint of obtaining optimal adsorption and residual adhesive inhibition, the weight-average molecular weight (Mw) of reactive MQ resin can be exemplified as 100 to 30,000, preferably 3,000 to 20,000, and more preferably 6,000 to 10,000.

[0053] In the crosslinking composition, the content of component (d) relative to 100 parts by weight of the total amount of components (a) and (b) can be 1.1 to 10.6 parts by weight. A content of 1.1 parts by weight or more of component (d) is preferred from the viewpoint of improving residual gum inhibition, while a content of 10.6 parts by weight or less is preferred from the viewpoint of improving the adsorption properties of the organosilicon adsorption layer. From the viewpoint of further obtaining these effects, a content of 1.1 to 1.5 parts by weight or 6 to 10.6 parts by weight, preferably 1.1 to 1.3 parts by weight or 9 to 10.6 parts by weight, is also preferred.

[0054] Furthermore, in the crosslinking composition, the content of component (d) relative to 100 parts by weight of component (c) can be 1 part by weight or more from the viewpoint of improving residual adhesive inhibition, and 11 parts by weight or less from the viewpoint of improving the adsorption of the organosilicon adsorption layer. From the viewpoint of further and more preferably obtaining these effects, the content of component (d) relative to 100 parts by weight of component (c) can be preferably 1 to 2 parts by weight or 8 to 11 parts by weight, and more preferably 1 to 1.5 parts by weight or 9 to 11 parts by weight.

[0055] (Other ingredients) In addition to components (a) to (d) above, the crosslinking composition may include, as needed, catalysts for addition reactions, solvents, etc.

[0056] Platinum group catalysts can be cited as catalysts for addition reactions. Specific examples of platinum group catalysts include chloroplatinic acid, chloroplatinic acid and other chloroplatinic acids, alcohols and aldehydes of chloroplatinic acid, and chain salts of chloroplatinic acid and various alkenes. These catalysts for addition reactions can be used alone or in combination. The amount of catalyst used for addition reactions, relative to 100 parts by weight of the total amount of component (a) and component (b), can be, for example, 1.5 to 2.5 parts by weight.

[0057] From the viewpoint of viscosity adjustment of crosslinking compositions, solvents can be used. Specific examples include aromatic hydrocarbon solvents such as toluene and xylene, aliphatic hydrocarbon solvents such as hexane, heptane, octane, and isoalkanes, ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone, ester solvents such as ethyl acetate and isobutyl acetate, and ether solvents such as diisopropyl ether and 1,4-dioxane. These solvents can be used alone or in combination. The amount of solvent used in the crosslinking composition can be, for example, 25-40% by weight, preferably 30-40% by weight. It should be noted that the crosslinking composition can be any of the following: solvent-free, solvent-based, or emulsion-based, and therefore can be solvent-free.

[0058] (thickness) The thickness of the silicone adsorption layer can be appropriately set by those skilled in the art to ensure the shear force of the silicone adsorption layer relative to the adhesive surface in the direction of the bonded body. Furthermore, from the viewpoint of improving the adsorption properties of the silicone adsorption layer, a thickness of 10 μm or more is preferred, more preferably 15 μm or more, further preferably 20 μm or more, and even more preferably 25 μm or more is desirable. From the viewpoint of improving residue suppression, a thickness of 50 μm or less is preferred, more preferably 30 μm or less, further preferably 25 μm or less, and even more preferably 20 μm or less is desirable.

[0059] (Formation method) The organosilicon adsorption layer can be formed on the substrate film constituting the above-mentioned substrate layer by forming a coating layer of the above-mentioned crosslinking composition through a crosslinking reaction.

[0060] Examples of coating methods for crosslinking compositions include roller coaters, bar coaters, float knife coaters, die coaters, gravure coaters, curtain coaters, and doctor blade coaters.

[0061] As for the crosslinking reaction conditions, there are no particular limitations as long as the conditions are such that component (a) and component (b) can be thermally crosslinked through an addition reaction. Examples of thermal crosslinking conditions are 160°C or below, with 100 to 160°C being preferred and 130 to 150°C being more preferred.

[0062] (Energy storage modulus) From the perspective of obtaining better adsorption and residual adhesive suppression, the storage modulus (G') of the organosilicon adsorption layer at 23°C can be 5 × 10⁻⁶. 4 ~15×10 4 From the viewpoint of further optimizing the adsorption properties, the storage modulus (G') of the organosilicon adsorption layer at 23°C is preferably 6.5 × 10⁻⁶. 4 ~15×10 4 Pa, more preferably 7×10 4 ~15×10 4 Pa, more preferably 7.5 × 10 4 ~15×10 4 Pa. Regarding the control of the energy storage modulus, for example, in the case of increasing the energy storage modulus, it can be controlled by increasing the blending ratio of component (c) and component (d), preferably by increasing the blending ratio of component (d), and in the case of decreasing the energy storage modulus, it can be controlled by decreasing the blending ratio of component (c) and component (d), preferably by decreasing the blending ratio of component (d). It should be noted that the energy storage modulus is a value measured by the method described in the examples.

[0063] (Adsorption and easy peeling) The silicone adsorption layer exhibits excellent adsorption properties relative to smooth surfaces, and on the other hand, it also possesses excellent properties of easy peeling after adsorption onto smooth surfaces (peelability). From the viewpoint of achieving even better adsorption and peelability, the peeling force of the silicone adsorption layer can be, for example, 350–7500 mN / 25 mm, preferably 500–6500 mN / 25 mm, and more preferably 800–5000 mN / 25 mm. By achieving such a peeling force, such as… Figure 6 As shown, when the silicone adsorption layer is fixed on the platform S of the abrasive member P (abrasive pad), even with high-speed abrasive operations, it is possible to maintain the properties of preventing partial peeling between the silicone adsorption layer 2 and the platform S, the ease of peeling the silicone adsorption film 10a from the platform S, and the ability to prevent residual adhesive on the platform S after peeling. It should be noted that the peeling force of the silicone adsorption layer is relative to the stainless steel surface, and specifically, it is a value measured by the method shown in the examples.

[0064] Adhesive layer The adhesive layer is provided for the purpose of bonding and fixing the grinding components.

[0065] Examples of adhesive compositions that can be used as adhesive layers include (meth)acrylic resins and isocyanate crosslinking agents.

[0066] Examples of (meth)acrylic resins include copolymers of alkyl (meth)acrylates without hydroxyl groups and monomers with hydroxyl groups.

[0067] Examples of alkyl groups in (meth)acrylates without hydroxyl groups include straight-chain or branched alkyl groups having 1 to 18 carbon atoms, preferably 1 to 8, and more preferably 1 to 4. Specific examples of (meth)acrylates without hydroxyl groups include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, and stearyl (meth)acrylate.

[0068] Examples of monomers containing hydroxyl groups include hydroxyalkyl methacrylates and other monomers containing hydroxyl groups. Examples of alkyl groups in hydroxyalkyl methacrylates include straight-chain or branched alkyl groups having 1 to 18 carbon atoms, preferably 1 to 8, and more preferably 1 to 4. Specific examples of hydroxyalkyl methacrylates include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 3-methyl-3-hydroxybutyl methacrylate, 1,1-dimethyl-3-hydroxybutyl methacrylate, 1,3-dimethyl-3-hydroxybutyl methacrylate, 2,2,4-trimethyl-3-hydroxypentyl methacrylate, and 2-ethyl-3-hydroxyhexyl methacrylate, among others. Other monomers containing hydroxyl groups include glycerol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, poly(ethylene glycol-propylene glycol) mono(meth)acrylate, N-hydroxymethylacrylamide, etc.

[0069] Examples of weight-average molecular weight (Mw) for (meth)acrylic resins include 100,000 to 1,000,000, preferably 300,000 to 800,000, and more preferably 400,000 to 600,000.

[0070] Examples of isocyanate-based crosslinking agents include hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, triisocyanate such as tris(phenylisocyanate) (トリス(フェニルイソシアネート)チオフォスフェート), and polyisocyanates that are isocyanurates.

[0071] Examples of thicknesses for the adhesive layer include 30 to 150 μm, and more preferably 40 to 80 μm.

[0072] In the method of laminating adhesive layers, an adhesive composition can be applied and dried on a substrate layer in which an organosilicon adsorption layer is laminated to form a coating layer. Alternatively, an organosilicon adsorption laminate of a substrate layer and an organosilicon adsorption layer can be prepared, and a cover film can be prepared. An adhesive composition is applied and dried on the release layer of the cover film to form a coating layer. The substrate layer side of the organosilicon adsorption laminate is then laminated with the coating layer facing each other.

[0073] Anchoring layer An anchoring layer, provided as needed, can be used to improve the adhesion between the substrate layer and the silicone adsorption layer, or to facilitate smooth peeling of the silicone adsorption film from a smooth surface without separation between the substrate layer and the silicone adsorption layer during peeling. An anchoring layer is particularly useful when the silicone adsorption layer and the substrate layer are a combination that is difficult to directly bond. Conversely, when the silicone adsorption layer and the substrate layer are a combination that is easy to directly bond, an anchoring layer may or may not be provided.

[0074] Materials that can be used as anchoring layers include polyester resins, acrylic resins, and polyurethane resins. From the viewpoint of antistatic properties and / or coating characteristics, acrylic resins are preferred as anchoring layer materials, and acrylic polyol resins are even more preferred.

[0075] Furthermore, the anchoring layer material may also contain an antistatic agent to further impart antistatic properties. Examples of antistatic agents include nonionic antistatic agents such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenols, polyoxyethylene alkylamines, polyoxyethylene alkylamides, polyethylene glycol esters of fatty acids, sorbitol esters of fatty acids, glycerol esters of polyoxyethylene fatty acids, and alkyl polyethyleneimine; acrylate-based antistatic agents such as acrylate compounds containing ethylene oxide; conductive polymers such as polyaniline, polypyrrole, polythiophene, poly3,4-ethylenedioxythiophene, and their derivatives; and conductive metal oxides such as antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), aluminum-doped zinc oxide, and antimony by-oxides. Conductive polymers are preferred, and polythiophene is more preferred. An anchoring layer incorporating an antistatic agent is particularly useful when using a substrate layer that does not possess antistatic properties. On the other hand, if the substrate layer itself has antistatic capabilities (e.g., the surface is treated with antistatic agents), an anchoring layer containing an antistatic agent may or may not be provided.

[0076] From the viewpoint of improving the adhesion between the substrate layer and the silicone adsorption layer, and from the viewpoint of further effectively obtaining antistatic ability while also imparting antistatic ability, the thickness of the anchoring layer can be, for example, 0.1 μm or more, preferably 1.0 μm or more. From the viewpoint of maintaining the overall flexibility of the silicone adsorption film so as to make it easier to stick and peel off relative to the smooth surface of the silicone adsorption film, the thickness can be, for example, 5.0 μm or less, preferably 3.0 μm or less.

[0077] An anchoring layer can be formed by coating a resin composition for anchoring layer containing the aforementioned materials, and then drying it to create a film. Examples of coating methods for the resin composition for anchoring layer include roller coaters, bar coaters, float coaters, die coaters, gravure coaters, curtain coaters, and doctor blade coaters.

[0078] Examples of methods for laminating anchoring layers include online methods that simultaneously fabricate and laminate the anchoring layer, and offline methods that separately fabricate the anchoring layer as a film before lamination.

[0079] Separating membrane A release liner is used to prevent dirt and foreign matter from adhering to the surface of the silicone adsorption layer, or to improve the operation of the silicone adsorption membrane. It is applied to the side of the silicone adsorption layer. The release liner can be used as follows: Figure 4 As illustrated in the example of the separator 20, it is a membrane composed of a substrate layer 5, or it can be like... Figure 5 As illustrated in the example of the release film 20a, it is a laminated film comprising a substrate layer 5 and a release layer 6 laminated on the substrate layer 5.

[0080] Examples of materials that can be used as the substrate layer in the release membrane include silicone-based release agents and fluorinated release agents, with release agents containing fluorinated silicone being a preferred choice. The thickness of the substrate layer is also the same as that of the substrate layer in the silicone adsorption membrane.

[0081] Examples of release agents that can be used as the release layer material in a release film include silicone-based release agents and fluorinated release agents, with fluorinated release agents being the preferred choice. Examples of fluorinated release agents include resin compositions for release layers comprising copolymers of fluoroolefins, cyclohexyl acrylates, and hydroxyl-containing vinyl ethers, and isocyanate-based crosslinking agents (such as hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, triisocyanates such as trithiophosphate tris(phenylisocyanate), and polyisocyanates containing isocyanurates).

[0082] As a method for forming a release layer, it can be formed by forming a coating layer of a release layer resin composition on a substrate film constituting the above-mentioned substrate layer and then carrying out a crosslinking reaction. Examples of coating methods for the release layer resin composition include roller coaters, bar coaters, float coaters, die coaters, gravure coaters, curtain coaters, and doctor blade coaters.

[0083] Examples of thicknesses for the release layer include 0.05 to 0.5 μm, and more preferably 0.1 to 0.3 μm.

[0084] Covering film Covering membrane such as Figure 2 As shown in the silicone adsorption film 10a, it is used to protect the adhesive layer of the silicone adsorption film having the adhesive layer 3 during the period up to the bonding of the grinding member, by adhering it to the adhesive layer side. The cover film is as follows: Figure 4 and Figure 5 As exemplified by the cover film 30, it is preferably a laminated film comprising a substrate layer 7 and a release layer 8 laminated on the substrate layer 7.

[0085] The material used as the substrate layer in the cover film is the same as that used as the substrate layer in the silicone adsorption film. The thickness of the substrate layer is also the same as that of the substrate layer in the silicone adsorption film. Examples of materials used as the release layer in the cover film include silicone-based release agents and fluorinated release agents, with silicone-based release agents being preferred. Examples of thicknesses for the release layer include, for example, 0.05–0.5 μm, preferably 0.1–0.3 μm.

[0086] How to use The organosilicon adsorption membrane of the present invention, for example... Figure 6 As shown, the polishing pad is fixed between the platform S of the polishing apparatus and the polishing member P (polishing pad). Examples of substrates that can be polished by the polishing member P include semiconductor wafers, hard disk substrates, and glass substrates for displays, which are polished during the manufacturing processes of semiconductor and electronic components. The silicone adsorption film of the present invention has excellent adsorption properties, and therefore is particularly preferred for high-speed polishing. Regarding the degree of high-speed polishing, examples of 80-100 rpm, preferably 85-95 rpm, are given for the rotational speed of the polishing platform with the polishing member fixed, and examples of 80-100 rpm, preferably 85-95 rpm, are given for the rotational speed of the polishing head with the polishing object fixed. The polishing platform with the polishing member fixed and the polishing head with the polishing object fixed rotate in the same direction. Example

[0087] The present invention is described in detail below with examples and comparative examples, but the invention is not limited to the examples described below. It should be noted that "parts" in the examples refer to parts by weight unless otherwise specified. Furthermore, the weight-average molecular weight is a polystyrene conversion value calculated using a Waters GPC measuring machine (model: Waters 410).

[0088] 1. Materials for organosilicon adsorption membranes 1-1. Film for substrate layer A 50 μm thick polyethylene terephthalate (PET) film was used, with both sides treated by plasma. The surface resistivity of this PET film was 5.1 × 10⁻⁶. 11 Ω / □.

[0089] 1-2. Crosslinking composition for organosilicon adsorption layer The crosslinking composition for preparing the organosilicon adsorbent layer with the composition shown in Table 1 was prepared. It should be noted that, as component (a), i.e., "crosslinking organopolysiloxane", a diorganopolysiloxane containing two or more alkenyl groups in one molecule with a weight average molecular weight of 77,844 was used; as component (b), i.e., "crosslinking agent", an organohydrogen polysiloxane with a weight average molecular weight of 1,240 was used; as component (c), i.e., "non-reactive MQ resin", a non-reactive MQ resin with a weight average molecular weight of 175,000 was used; as component (d), i.e., "reactive MQ resin", a reactive MQ resin with a weight average molecular weight of 6,610 was used; toluene was used as the solvent; and CAT.PL-56 (manufactured by Shin-Etsu Silicones Co., Ltd.) was used as the platinum catalyst.

[0090] 1-3. Resin composition for anchoring layer Prepare a resin composition for anchoring layers with the following composition.

[0091] 1-4. Adhesive Composition Prepare an adhesive composition with the following composition. · 100.0 parts of acrylic copolymer (Hydroxybutyl acrylate, butyl acrylate copolymer, weight average molecular weight Mw: approximately 500,000, solids content 37%) 0.05 parts of hexamethylene diisocyanate (Solid content 37.5%)

[0092] 2. Materials of the separator membrane 2-1. Film for substrate layer A polyethylene terephthalate film with a thickness of 50 μm was used.

[0093] 2-2. Resin composition for release layer Prepare a resin composition for a release layer with the following composition.

[0094] 3. Materials of the covering membrane 3-1. Film for substrate layer A polyethylene terephthalate film with a thickness of 50 μm was used.

[0095] 3-2. Resin composition for release layer Use silicone-based mold release agents.

[0096] 4. Fabrication of the separating membrane On one side of a film (the material of the release film) used as a substrate layer, a resin composition for the release layer (the material of the release film) is applied using a die coater at 23°C and 50% RH. Then, the mixture is cross-linked at a dryer temperature of 150°C and a residence time of 100 seconds to form a 0.15 μm release layer, thus producing the release film. This release film is equivalent to... Figure 5 The isolation membrane 20a shown in the figure.

[0097] 5. Fabrication of the covering film A silicone-based release agent is coated on one side of a film used as a substrate layer (the material of the cover film) to form a 0.15 μm release layer, thus creating the cover film. This cover film is equivalent to... Figure 4 , 5 The covering film 30 shown.

[0098] 6. Fabrication of Organosilicon Adsorption Membranes (Example 5) On one side of a film (the material of the silicone adsorption film) used as a substrate layer, a crosslinking composition for setting the silicone adsorption layer is applied using a die coater at 23°C and 50% RH. Then, it is crosslinked in an oven at 150°C for 100 seconds to form a silicone adsorption layer of the thickness shown in Table 1. Thus, a silicone adsorption film with a silicone adsorption layer laminated on a substrate layer is produced. This silicone adsorption film is equivalent to... Figure 1 The organosilicon adsorption membrane 10 shown is shown.

[0099] With the release layer 6 of the release membrane 20a facing the silicone adsorption layer 2 of the silicone adsorption membrane 10, it is clamped by two rollers (a rubber roller and a metal roller) while allowing air to escape and bonding. Thus, a silicone adsorption membrane 10 with the release membrane 20a is obtained.

[0100] The adhesive composition is applied to the release layer 8 of the cover film 30 using a mold coating machine, and heated and dried at 100°C for 2 minutes to form an adhesive layer 3 with a thickness of 50 μm.

[0101] With the adhesive layer 3 formed on the cover film 30 facing the substrate layer 1 of the silicone adsorption film 10 with the release liner, it is clamped by two rollers (a rubber roller and a metal roller) and bonded while allowing air to escape. This yields a silicone adsorption film 10a further laminated with the adhesive layer 3. This silicone adsorption film 10a has a release liner 20a laminated on the silicone adsorption layer 2 side and a cover film 30 laminated on the adhesive layer 3 side (see reference). Figure 5 ).

[0102] (Examples 1-4 and 6-9, and Comparative Examples 1-3) On one side of the film (material of the silicone adsorption film) used as the substrate layer, a resin composition for the anchoring layer is coated using a gravure coating machine and dried to form an anchoring layer with a thickness of 2 μm. On the formed anchoring layer, a crosslinking composition for the silicone adsorption layer is coated using a die-coating machine at 23°C and 50% RH, and then crosslinked in an oven at 150°C for 100 seconds to form a silicone adsorption layer of the thickness shown in Table 1. Thus, a silicone adsorption film with a silicone adsorption layer laminated on a substrate layer via an anchoring layer is produced. This silicone adsorption film is equivalent to... Figure 3 The organosilicon adsorption membrane 10b shown is illustrated.

[0103] On the silicone adsorption layer 2 of the silicone adsorption membrane 10b, with the release layer 6 of the release membrane 20a facing each other, it is clamped by two rollers (a rubber roller and a metal roller) to bond them together while allowing air to escape. Thus, a silicone adsorption membrane 10b with the release membrane 20a is obtained.

[0104] The adhesive composition is applied to the release layer 8 of the cover film 30 using a molding machine, and then heated and dried at 100°C for 2 minutes to form an adhesive layer 3 with a thickness of 50 μm.

[0105] With the adhesive layer 3 formed on the cover film 30 facing the substrate layer 1 of the silicone adsorption film 10b with the release liner 20a, the film is held between two rollers (a rubber roller and a metal roller) and bonded together while allowing air to escape. This results in a silicone adsorption film with the adhesive layer 3 further laminated on top of the silicone adsorption film 10b. This silicone adsorption film has the release liner 20a laminated on the silicone adsorption layer 2 side and the cover film 30 laminated on the adhesive layer 3 side.

[0106] 7. Determination of the storage modulus of organosilicon adsorption layer A crosslinking composition for setting an organosilicon adsorption layer was applied to one side of a 50 μm thick fluororesin sheet using a die-coating machine at 23°C and 50% RH. The mixture was then crosslinked in an oven at 150°C for 100 seconds to form a 50 μm thick organosilicon adsorption layer. The resulting organosilicon adsorption layer was peeled off from the fluororesin sheet to prepare a test piece for viscoelasticity testing. Using a viscoelasticity testing machine (manufactured by Rheology Co., Ltd., trade name: MR-300), the test piece was clamped between the measuring section (parallel discs) of the machine, and the storage modulus (G') at 23°C was measured at a frequency of 1 Hz. The results are shown in Table 1.

[0107] 8. Evaluation of Organosilicon Adsorption Membranes 8-1. Adsorption Peeling off the cover film exposes the adhesive layer of the silicone adsorption membrane; peeling off the release film exposes the silicone adsorption layer of the silicone adsorption membrane. Figure 6As illustrated in the example, the silicone adsorption film is sandwiched between the polishing pad and the platform of the polishing apparatus such that the adhesive layer 3 side faces the polishing pad P and the silicone adsorption layer 2 side faces the platform S of the polishing apparatus, and the polishing pad is fixed on the platform of the polishing apparatus.

[0108] Using the polishing apparatus with the polishing pad fixed as described above, 10 pieces of objects to be polished were subjected to high-speed polishing. The polishing conditions are as described below. Polishing apparatus: FREX 300E manufactured by Ebara Corporation Polishing pad: IC1000 / SUBA400 (manufactured by Nitta Haas Inc.) Polishing pressure: 2.0 psi (1 psi = 6894.76 Pa, the same applies hereinafter) Polishing platform rotational speed: 90 rpm Carrier rotational speed: 91 rpm Supply of polishing composition: Gravity flow (continuous pouring) Polishing composition: 5% aqueous solution of silica slurry Object to be polished: Silicon wafer (φ300 mm) Polishing composition supply rate: 300 ml / min Polishing time: 10 minutes

[0109] After polishing, peeling of the silicone adsorption layer of the silicone adsorption film for fixing the polishing pad was visually confirmed, and the adsorptivity was evaluated based on the following criteria. The results are shown in Table 1. ◎: No peeling of the silicone adsorption layer, with excellent adsorptivity suitable for high-speed polishing. ○: Slight peeling at the end of the silicone adsorption layer, but no problem in practical use for high-speed polishing. ×: The silicone adsorption layer peels off, and cannot withstand practical use for high-speed polishing.

[0110] 8-2. Residual gum inhibition The silicone adsorption film 10 with the separator film 20a and 10b with the separator film 20a were cut into a shape of 100 mm in length × 25 mm in width to prepare evaluation specimens. The separator film 20a was peeled from the above specimen in an environment of 23° C. and 50% RH, the exposed surface of the silicone adsorption layer 2 was attached to a polished stainless steel plate (SUS plate), pressed by a 2 kg roller for one reciprocation, and left to stand for 24 hours in an atmosphere of 23° C. Thereafter, using a tensile tester, peeling was performed at a peeling angle of 180° and a peeling speed of 300 mm / min, the contamination (adhesive residue) on the surface of the SUS plate was visually observed, and evaluation was performed according to the following criteria. The evaluation results are shown in Table 1. ◎: No adhesive residue is observed on the SUS plate at all, achieving extremely excellent reworkability. ○: There is a slight amount of adhesive residue on the SUS board, but the reprocessability is good and there are no practical problems. ×: Significant adhesive residue exists on the SUS board, making it unsuitable for practical use.

[0111] 8-3. Ease of peeling An organosilicon adsorption membrane with an organosilicon adsorption layer laminated via the aforementioned anchoring layer was fabricated on a 100 μm thick polyester film. This organosilicon adsorption membrane was cut into a shape 100 mm long × 25 mm wide to prepare an evaluation sample. The organosilicon adsorption layer of the evaluation sample was attached to a 2 mm thick polished stainless steel plate (SUS plate), and pressed back and forth once by a 2 kg roller. The plate was then placed at 23°C for 24 hours. Next, a tensile testing machine was used to peel the stainless steel plate at a peel angle of 180° and a peel speed of 1200 mm / min, and the peel force (mN / 25 mm) was measured. The test results are shown in Table 1. Furthermore, based on the test results, the peelability was classified and evaluated in order of superiority as "++++" (below 100mN / 25mm), "++" (above 100mN / 25mm but below 800mN / 25mm), "++" (above 800mN / 25mm but below 2200mN / 25mm), "+" (above 2200mN / 25mm but below 5000mN / 25mm), and "-" (above 5000mN / 25mm). The evaluation results are shown in Table 1.

[0112] [Table 1]

[0113] As shown in Table 1, in an organosilicon adsorption film comprising a substrate layer and an organosilicon adsorption layer stacked on the substrate layer, wherein the organosilicon adsorption layer is a cured product of a crosslinking composition comprising (a) a crosslinking organopolysiloxane and (b) a crosslinking agent, the crosslinking composition, when it does not contain either or both of (c) a non-reactive MQ resin and (d) a reactive MQ resin (Comparative Examples 1-3), cannot simultaneously achieve the adsorption and residual adhesive inhibition properties of the organosilicon adsorption layer in the organosilicon adsorption film. However, when the crosslinking composition contains both (c) a non-reactive MQ resin and (d) a reactive MQ resin (Examples 1-9), it can simultaneously achieve the adsorption and residual adhesive inhibition properties of the organosilicon adsorption layer in the organosilicon adsorption film. Explanation of reference numerals in the attached figures

[0114] 10, 10a, 10b… Organosilicon adsorption membranes 1…Substrate layer 2…organosilicon adsorption layer 3… Adhesive layer 4… Anchoring layer 20, 20a… separator membrane 5…Substrate layer 6… Release layer 30… Covering film 7…Substrate layer 8… Release layer S… platform P…Abrasive component (abrasive pad).

Claims

1. An organosilicon adsorption membrane, comprising a substrate layer, an organosilicon adsorption layer laminated on one side of the substrate layer, and an adhesive layer located on the other side of the substrate layer. The substrate layer is made of polyolefin, polyester, polyamide, polycarbonate, triacetyl cellulose, fluoropolymer, polyphenylene ether, polyimide, polyamide-imide, acrylic resin, polyvinyl chloride, polyvinylidene chloride, or polyacrylonitrile. The organosilicon adsorption layer is a cured product of a crosslinking composition, which comprises (a) a crosslinked organopolysiloxane, (b) a crosslinking agent, (c) a non-reactive MQ resin, and (d) a reactive MQ resin. The content of component (b) is such that 1 mole of component (a) results in 0.5 to 4 moles of hydrogen atoms in component (b). Relative to the total amount of component (a) and component (b) 100 parts by weight, the product includes 43 to 100 parts by weight of component (c) and 1.1 to 10.6 parts by weight of component (d). The thickness of the organosilicon adsorption layer is 10–50 μm. The silicone adsorption membrane is used to fix the silicone adsorption layer on the platform of the grinding device and to fix the grinding pad on the adhesive layer side.

2. The organosilicon adsorption membrane according to claim 1, wherein, The component (a) is a diorganopolysiloxane containing two or more alkenyl groups in one molecule.

3. The organosilicon adsorption membrane according to claim 1 or 2, wherein, The component (b) is an organohydrogen polysiloxane.

4. The organosilicon adsorption membrane according to claim 1 or 2, wherein, The thickness of the organosilicon adsorption layer is 15-30 mm. μ m.

5. The organosilicon adsorption membrane according to claim 1 or 2, wherein, The energy storage modulus of the organosilicon adsorption layer is 5×10⁻⁶. 4 ~15×10 4 Pa.

6. The organosilicon adsorption membrane according to claim 1 or 2, wherein, An anchoring layer is included between the substrate layer and the silicone adsorption layer, the anchoring layer being selected from polyester resins, acrylic resins and polyurethane resins.

Citation Information

Patent Citations

  • Polishing pad

    JP2014108498A

  • Silicone adsorptive film

    JP2019077750A